2020
DOI: 10.7150/ijms.45256
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA LINC01503 promotes the progression of hepatocellular carcinoma via activating MAPK/ERK pathway

Abstract: Background: Increasing evidence has implicated that lncRNAs (long non-coding RNAs) play significant roles in carcinogenesis and progression of HCC (hepatocellular carcinoma). LINC01503 is a new lncRNA related to several tumors. Nonetheless, its role in HCC still remains unclear. Methods: The expression levels of LINC01503 in HCC, normal liver tissues as well as HCC cell lines were evaluated by TCGA (The Cancer Genome Atlas) and real-time PCR assay, respectively. The relationship between LINC01503 levels and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Transcripts with no apparent protein-coding potential, which are larger than 200 nucleotides, are defined as long noncoding RNAs (lncRNAs) [3]. Increasing evidence has demonstrated that lncRNAs play essential roles in the initiation and progression of human cancers via regulating several cellular behaviors, including proliferation, apoptosis, migration, invasion, and glycolysis [4,5]. Our group Ivyspring International Publisher has previously identified several HCC-related lncRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Transcripts with no apparent protein-coding potential, which are larger than 200 nucleotides, are defined as long noncoding RNAs (lncRNAs) [3]. Increasing evidence has demonstrated that lncRNAs play essential roles in the initiation and progression of human cancers via regulating several cellular behaviors, including proliferation, apoptosis, migration, invasion, and glycolysis [4,5]. Our group Ivyspring International Publisher has previously identified several HCC-related lncRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Upregulated expression of lncRNA LASTR was found in several epithelial tumors and could facilitate cancer cell fitness in hypoxic breast cancer through SART3 ( De Troyer et al, 2020 ). LINC01503 is involved in a variety of malignancies, including hepatocellular carcinoma, cholangio-carcinoma, non-small-cell lung cancer, cervical cancer, and gastric cancer ( Qu et al, 2019 ; Shen et al, 2020 ; Wang et al, 2020 ; Zhang et al, 2020 ; Feng et al, 2021 ; Ma et al, 2021 ). Wu et al (2021) reported that the overexpression of LINC00460 in pancreatic ductal adenocarcinoma could promote tumor aggressiveness by targeting miR-491-5p, conferring a poor clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Dong et al [ 36 ] further demonstrated that LINC00899 promoted cell proliferation and inhibited apoptosis in AML cells. LINC01503 expression level was significantly up-regulated, correlated with poor prognosis and conferred oncogenic functions in glioma [ 37 ], hepatocellular carcinoma [ 38 ], gastric cancer [ 39 ] and especially colorectal cancer [ 40 ]. Silencing of PRKAG2-AS1 alleviated castration-resistant prostate cancer (CRPC) tumor growth, showing repression of androgen receptor (AR) and AR variant expression [ 41 ].…”
Section: Discussionmentioning
confidence: 99%